Fiber tortuosity and its effects on shock transfer characteristics of Ultra High Molecular Weight Polyethylene (UHMWPE) fibers embedded in a polyurethane composite structure. (26th May 2020) - Anwer, Ahmed A.W.; Dong, Tony; Naguib, Hani E.
Abstract: Low density, high strength, and flexibility of ultra-high molecular weight polyethylene (UHMWPE) fibers have made them a topic of intensive research in many fields. More specifically, UHMWPE has been extensively used in shock damping applications. However, little is known about the effects of fiber tortuosity and fiber wetting on the shock transfer characteristics of these fibers. Herein, focus is placed on studying the effects of tortuosity and fiber wetting on the shock transfer characteristics of UHMWPE fiber braid embedded in a polyurethane matrix. Shock transfer characteristics of these fibers are identified by generating a longitudinal shock on one end of the fiber, while simultaneously measuring the transferred force overtime on the other side of the fiber. From the experiments it is found that the force versus time response of these structures show an underdamped response. Analyzing the maximum force transfer and the rate of decay, it is seen that tortuosity has a significant effect on the shock transfer characteristics of these structures. Given the nature of these results, it is strongly believed that the presented work provides a creative strategy for designing, developing, and characterizing, new composite structures with improved impact attenuation characteristics.